2014
DOI: 10.2174/1874325001408010007
|View full text |Cite
|
Sign up to set email alerts
|

The Truth Behind Subchondral Cysts in Osteoarthritis of the Knee

Abstract: Background:Subchondral cysts have always been taught to be one of the cardinal radiological features of knee osteoarthritis but are not well understood. We aimed to evaluate the radiological prevalence and epidemiology of subchondral cysts in patients with knee osteoarthritis to determine if they are truly a cardinal radiological feature.Methods:All patients of a single surgeon with symptoms of knee osteoarthritis were selected for this study. All patients had failed a trial of conservative therapy and were pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 17 publications
1
37
1
1
Order By: Relevance
“…The discrepancy in gender difference and age correlation between STB and DTB may be due to the distinct roles of these two structures in maintaining joint homeostasis. Consistent with previous studies [52][53][54][55][56], our study also showed a high frequency of SBC in late-stage OA. However, the frequency of cysts in DTB was much lower compared to that in STB.…”
Section: Discussionsupporting
confidence: 93%
“…The discrepancy in gender difference and age correlation between STB and DTB may be due to the distinct roles of these two structures in maintaining joint homeostasis. Consistent with previous studies [52][53][54][55][56], our study also showed a high frequency of SBC in late-stage OA. However, the frequency of cysts in DTB was much lower compared to that in STB.…”
Section: Discussionsupporting
confidence: 93%
“…Then, the bone starts the healing process by resorbing the necrotic areas, which provide a passage for the synovial fluid to intrude into the bone, resulting in subchondral cyst formation. 33 …”
Section: Discussionmentioning
confidence: 99%
“…They can present in conditions such as osteoarthritis, rheumatoid arthritis, calcium pyrophosphate deposition disease, and osteonecrosis, but still the physiopathologic process is unclear. 1 Two theories have been postulated: the synovial intrusion theory and the bony contusion theory. The first suggests a connection between the articular and cystic cavities that allows the synovium to enter and enlarge the defect.…”
mentioning
confidence: 99%
“…The necrotic area is further remodeled with bone fragments phagocytosed by osteoclasts, creating a subchondral cystic cavity. 1 , 2 , 3 …”
mentioning
confidence: 99%